Evaluación de la Resistencia de Viga Soldada de la Estructura del Hotel “San Carlos” (2007)
The Hotel San Carlos is subject to a reshaping and like part of this one the beams of armed concrete, which is over the "Lobby" will be reinforced by beams of profile steel IPN - 300 laminated ones in warm normalized as “Europaean Standard Beams”. The laying of one of the beams of provoca in the investors certain suspense since there appears a reinforced welded union where there meet three types different from unions welded in the union, each of which will support a part of the load assigned to the same one. Since there developed in this work a method of Calculation that it allows to determine that it departs from the applied carrying capacity it is assimilated by each of the component parts of a mixed union as the analyzed one in the welded beam of the structure of the Hotel “San Carlos”. The developed Method was validated by means of the comparison of the results obtained by the analytical expressions proposed with the results obtained by the Method of the Finite Elements, a very good congruity being obtained.